Asymmetric distribution of TLR3 leads to a polarized immune response in human intestinal epithelial cells - Stanifer, Megan; Mukenhirn, Markus; Münchau, Stephanie; Pervolaraki, Kalliopi; Kanaya, Takashi; Albrecht, Dorothee; Odendall, Charlotte; Hielscher, Thomas; Haucke, Volker; Kagan, Jonathan C.; Bartfeld, Sina; Ohno, Hiroshi; et al. (Nature microbiology, 2020)
Viral infection from the basolateral side of intestinal epithelial cells (IECs) is shown to elicit a stronger intrinsic immune response than apical infection, an effect driven by the polarized sorting of Toll-like receptor 3. Experiments in mice and human cells suggest that the cellular polarity program is integral to the ability of IECs to tolerate gut commensals while remaining responsive to invasive pathogens.
Published online: 4 November 2019
Gesehen am 07.04.2020